T‐cell diversification reflects antigen selection in the blood of patients on immune checkpoint inhibition and may be exploited as liquid biopsy biomarker. Issue 11 (6th March 2017) - Akyüz, Nuray; Brandt, Anna; Stein, Alexander; Schliffke, Simon; Mährle, Thorben; Quidde, Julia; Goekkurt, Eray; Loges, Sonja; Haalck, Thomas; Ford, Christopher Thomas; Asemissen, Anne Marie; Thiele, Benjamin; et al.
Abstract : Cancer immunotherapy with antibodies targeting immune checkpoints, such as programmed cell death protein 1 (PD‐1), shows encouraging results, but reliable biomarkers predicting response to this costly and potentially toxic treatment approach are still lacking. To explore an immune signature predictive for response, we performed liquid biopsy immunoprofiling in 18 cancer patients undergoing PD‐1 inhibition before and shortly after initiation of treatment by multicolor flow cytometry and next‐generation T‐ and B‐cell immunosequencing ( TCRß / IGH ). Findings were correlated with clinical outcomes. We found almost complete saturation of surface PD‐1 on all T‐cell subsets after the first dose of the antibody. Both T‐ and B‐cell compartments quantitatively expanded during treatment. These expansions were mainly driven by an increase in the activated T‐cell compartments, as well as of naïve B‐ and plasma cells. Deep immunosequencing revealed a clear diversification pattern of the clonal T‐cell space indicative of antigenic selection in 47% of patients, while the remaining patients showed stable repertoires. 43% of the patients with a diversification pattern showed disease control in response to the PD‐1 inhibitor. No disease stabilizations were observed without clonal T‐cell space diversification. Our data show for the first time a clear impact of PD‐1 targeting not only on circulating T‐cells, but also on B‐lineage cells, shedding light on the complexity of the anti‐tumor immune response. Liquid biopsy T‐cell next‐generation immunosequencing should be prospectively evaluated as part of a composite response prediction biomarker panel in the context of clinical studies. Abstract : What's new? Blocking immune‐checkpoint receptors on T cells may enhance the immune response against tumor cells. Clinical results for antibodies that target these receptors have been encouraging, but the treatments are costly and potentially toxic. Biomarkers that help predict response to treatment are thus urgently needed. In our study using blood from patients undergoing anti‐PD1 immunotherapy, the authors identified specific "TCRß immune signatures" that correlated with a good response to therapy about half the time. These expression signatures may thus represent a promising predictive biomarker and should be tested further.